Optimization of Starter Motor for Automobile Applications - Sarathkkumar V K; Jeya Paul Singh N; Pushparajesh V (Journal of Electronic Design Engineering, 2017)
Normally, both brushed dc Motor and brushless dc motor are used as a starter motor in the automobile application. This paper presents the optimization methodology for brushed PM dc motors. In this brushed dc motor will be a four pole twenty-five slots based machine. This model analysis involves the more number of analytical calculations and computation for the selection of the best model, performance and excellent material characteristics. This method is considered with the existing commercial dc motors to meet the same performance after reduction of weight with change of some parameters; for cranes to lift the loads, various trucks, drill hand tool and automotive application likes car, bike. Optimised DC machine designs using Ferrite permanent magnets are proposed and provide important size and weight reductions without losing of its performance. The finalized model and the existing model was solved using the MAGNET Software by FEA (Finite Element Analysis) to see the basic performance such as flux density, speed, torque, output power of the existing model.